Pemberdayaan anak jalanan - Sri Kushartati (Universitas Ahmad Dahlan, 2004)
The number of street children increasing in this last decade is our big problem due to any problem appearing. This study was conducted using one of qualitative research, called action research. Action research is a research, developed by researcher together with the decision maker. This is in accordance with the aim of this study. The aim of this study is to understand street children situation and condition as a consideration to decide strategies in conducting intervention program, especially for empowering stret children.Â